Em que gênero eu canto? A operação do gênero na construção de performances vocais de cantoras e cantores transgêneros - Caldeira, Bruno (2021)
This paper aims at unveiling gender operation in the construction of transgender singers vocal performances. Therefore, departing from the hypothesis in which people construct their vocal performances based on a “gendered vocal aesthetic”. In this context, the concepts of music as a social practice (GREEN, 1987 apud SOUZA, 2014; KRAEMER, 2000), gender as a social construction (BUTLER, 2003; 2014; BENTO (2006) and socialization (BERGER; LUCKMANN, 2004; SETTON, 2002; 2009; 2011) were taken as a theoretical reference in this research. As a method, it was adopted the perspective of case study as a theoretical construct (WALTON, 2009; RAGIN, 2009) and comprehensive interview as an instrument of data collecting (KAUFMANN, 2013). This paper proposes that, having a base for gender vocal aesthetic, that has values and meaning to voices based on binary masculinity and femininity standards, individuals construct vocal habitus from which they construct vocal performances that, in the beginning, need to frame in vocal masculinity and femininity standards naturalized by gender operations in voices.